Role-player expectations regarding the education of nursing research - Zeelie, S C; Bornman, J E; Botes, A C (Curationis (Pretoria), 2003)
This article reports on role player expectations regarding the education of nursing research. The importance of the role player expectations are two-fold: firstly as a factor in the external environment influencing and guiding the formulation phase of the development of standards and secondly, due to the clear indications of problems regarding nursing research in the nursing profession in literature. The role player expectations were elicited using a qualitative, exploratory and contextual design. The role player population included nurse educators, nurses in managerial, clinical and research positions, students and the medical profession. The data was gathered using the naïve sketches and qualitative data analysis was done using Morse & Field's approach (1996:103-107) in combination with Tesch's data analysis approach as cited by Creswell (1994:154-156). Sixty initial categories were narrowed down to six final categories, which are the research learning programme, personnel, students, departmental policies, funding and support systems. The role player expectations were elicited as part of a research study aiming tot develop a self-evaluation system for quality assurance in nursing research and as such, the role player expectations plays a pivotal role in the development of standards for the self-evaluation system.